Influence of Different Soil Mixtures on Nursery Growth of some Arid Zone Tree Species - Gupta, G. N. (Indian Forester, 1992)
Arid regions of Rajasthan are predominantly occupied by sandy soil. The nursery stock raised on such soil is poor and often results in heavy mortality when out planted. Therefore, a nursery experiment was conducted by mixing different levels of tank silt (0,5,10 and 20%), farm yard manure (0,2,4 and 6%), nitrogen (0,10,20 and 40 ppm as urea) and phosphorus (0,15 and 30 ppm P.O as single superphosphate) to findout the suitable mixture for producing healthy seedlings of some arid zone tree species. The study indicated significant influence of mixing tank silt and FYM, with sand, on the seedling growth of Dalbergia sissoo, Albizia lebbek and Prosopis cineraria. Response to nitrogen application was shown only by Albizia lebbek. None of the species responded to phosphate application. The potting mixture producing the best healthy seedlings in this study were, 10 percent tank silt + 2 percent FYM for Dalbergia sissoo, 10 percent tank silt + 4 percent FYM + 40 ppm nitrogen for Albizia lebbek and 10 percent tank silt for Propsis cineraria. Use of tank silt improved the aggregation and the mixture remained intact with the seedling when polythene bag was removed.